Improving The Geotechnical Properties of Cohesive Soils Using Portland Cement and Some Composite Polymers in A Selected Location in The City of Tanumah / Basrah Governorate – Southern Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The purpose of this research is to ascertain how adding Portland cement and composite polymers, as well as the ideal ratios between them, will affect cohesive soils' geotechnical characteristics. Materials and Methods:A composite polymer was created by combining three polymers—isocyanide, unsaturated polyester, polyvinyl acetate, and thinner—as well as a solvent. Portland cement was added to the soil at a rate of 5% of the sample weight. Different percentages of the weight of the cement supplied to the sample—5, 10, 15, 20, and 25%—were utilized as the composite polymer. Several geotechnical tests were carried out, including compaction, unconfined compressive strength, California bearing ratio, absorption, and Atterberg's limits, to ascertain the ideal amount of polymer for the aim of improvement.Results:The findings show that adding cement at a rate of 5% by weight of the sample and a polymeric mixture at a rate of 15% by weight of cement can improve the cohesive soil's engineering properties. It was found that the maximum dry density, unconfined compressive strength, and California bearing ratio had increased while the values of the optimal moisture content, absorption rate, liquid limit values, and plasticity index had decreased.Conclusion:The composite polymer used in soil improvement not only improves the geotechnical properties and resistance of the soil, but it also efficiently enhances and activates the effectiveness of cement. When 15% of the sample's weight of cement was composed of composite polymers, the soil's engineering attributes increased the most.